The effect of Fixed Partial Dentures on Periodontal Status of Abutment Teeth - Jebin, Farkhanda Mah; Jobayer, Tareq Bin; Habib, Md Ahsan; Islam, Md Shahidul; Nahar, Kamrun (KYAMC Journal, 2025)
Background: The fixed partial denture (FPD) is a common treatment available for restoring partially edentulous ridges. The gingival tissues should exhibit scalloped margins, a sulcus depth within the 1–3 mm range, and an adequate width of attached gingiva. The most important factor controlling the effects of restorations on gingival health is the location of the crown margin related to the gingival margin. Objective: The study was to assess the periodontal status of adult patients at the Military Dental Center, Dhaka, who received regular oral prophylaxis following the insertion of fixed partial dentures. Materials and Methods: The study sample included 78 adult patients with fixed partial dentures from the Military Dental Center in Dhaka. One calibrated examiner assessed and recorded the plaque index, the gingival index, probing pocket depth, and the crown margin locations. Results: The abutment teeth scored significantly higher plaque and gingival indices and greater probing pocket depth than non-abutment teeth. In addition, the abutment teeth scored the greatest mean values of the clinical parameters in subjects who were 46 years old or older and those who had their functioning fixed partial dentures for more than 5 years. The teeth with supra-gingivally placed crown margins had significantly higher mean values of plaque index, gingival index and probing pocket depth than teeth with sub-gingival crown margins. The results of this study indicated that in subjects with fixed partial dentures, the abutment teeth are more prone to periodontal inflammation than the non-abutment teeth. Conclusion: In subjects with fixed partial dentures, the abutment teeth are more prone to periodontal inflammation than the non-abutment teeth. Additionally, the individual’s age, duration of insertion of fixed partial dentures, and location of the crown margins also affect the periodontal health of the abutments. KYAMC Journal Vol. 15, No. 04, January 2025: 184-188